PENINGKATAN KETERAMPILAN MENGIDENTIFIKASI UNSUR INTRINSIK CERPEN MENGGUNAKAN MODEL KOOPERATIF TIPE PAIR CHECK - Yusvia, Dona Yolanda; Martono, Martono; Priyadi, A. Totok (Universitas Tanjungpura, 2019)
AbstractA general problem in this research is how the improvement of identifying the intrinsic elements skills of short story using the cooperative model type of Pair Check at the students of XI IS4 SMA Santu Petrus Pontianak?